(untitled) (Foro de Educacion, 2024)
Commentators did their best to bury the late Oriana Fallaci’s ideas and books written since the 11 S under tons of praises to her previous works, and under deep silence or global discrediting her denunciation of Islamic fundamentalism and of terrorist blackmail and all its forms of getting a grip on Europe. Obituary notices avoided carefully the analysis of facts and data brought forward by Oriana in her three last books: The rage and the pride. The power of the reason and Oriana Fallaci’s inter- view with herself. The Apocalypse. But the italian journalist, who past away on 15th Sep- tember 2006, denounced substantiated facts, true dangers and a real collusion of wes- tern sectors-venal, corrupt, fainthearted and ignorant-with the strategy of penetration and manipulation of public opinion of an islamic movement who is the enemy of democracies, Civil Rights, freedom and the western systems of open society.